2000
DOI: 10.1093/brain/123.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Language lateralization in healthy right-handers

Abstract: Our knowledge about the variability of cerebral language lateralization is derived from studies of patients with brain lesions and thus possible secondary reorganization of cerebral functions. In healthy right-handed subjects 'atypical', i.e. right hemisphere language dominance, has generally been assumed to be exceedingly rare. To test this assumption we measured language lateralization in 188 healthy subjects with moderate and strong right-handedness (59% females) by a new non-invasive, quantitative techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
281
3
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(314 citation statements)
references
References 56 publications
(67 reference statements)
18
281
3
5
Order By: Relevance
“…The left hemispheric lateralization of greater alpha activity in the insula/vlPFC during negative compared to positive visualisation is unlikely to be specifically associated with feelings of urge or craving per se, as previous studies have not suggested lateralization of these processes (Naqvi & Bechara, 2008;Naqvi, Rudrauf, Damasio & Bechara, 2007). A more apposite explanation is that the observed left lateralization is related to language processing, for which the left hemisphere is dominant (Knecht et al, 2000), and the participants' conscious experience of their urge to neutralize. The forms of cognitive reappraisal which were endorsed by participants are likely to have involved sub-vocalisation, which is consistent with the role of left lateralized insula, and particularly vlPFC, in 'inner speech' (Morin, 2009;Riecker, Ackermann, Wildgruber, Dogil & Grodd, 2000) which appears to be crucial to the experience of self-conscious emotions (Jones & Fernyhough, 2007;Morin, 2009;Morin & Michaud, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…The left hemispheric lateralization of greater alpha activity in the insula/vlPFC during negative compared to positive visualisation is unlikely to be specifically associated with feelings of urge or craving per se, as previous studies have not suggested lateralization of these processes (Naqvi & Bechara, 2008;Naqvi, Rudrauf, Damasio & Bechara, 2007). A more apposite explanation is that the observed left lateralization is related to language processing, for which the left hemisphere is dominant (Knecht et al, 2000), and the participants' conscious experience of their urge to neutralize. The forms of cognitive reappraisal which were endorsed by participants are likely to have involved sub-vocalisation, which is consistent with the role of left lateralized insula, and particularly vlPFC, in 'inner speech' (Morin, 2009;Riecker, Ackermann, Wildgruber, Dogil & Grodd, 2000) which appears to be crucial to the experience of self-conscious emotions (Jones & Fernyhough, 2007;Morin, 2009;Morin & Michaud, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…There is also a weak correlation between handedness and the lateralized representation of language in the human brain. Studies based on the Wada test (Rasmussen & Milner 1977), electroconvulsive therapy (Warrington & Pratt 1973) and brain imaging (Pujol et al 1999;Knecht et al 2000) are reasonably consistent in showing that over 90 per cent of right-handers are left-cerebrally dominant for language, compared with approximately 70 per cent of left-handers. These estimates can be matched by McManus's model with p(D)Z0.8, on the assumption that handedness and cerebral dominance for language are subject to the same biases in the three genotypes, but that the biases are applied independently (table 2).…”
Section: Genetic Theoriesmentioning
confidence: 92%
“…Right handedness presumably reflects a left-hemisphere specialization for motor skills and is thought to be an indirect marker of lateralization for language functions. For example, 96% of righthanded individuals are left-hemisphere dominant for language in contrast to about 70% in lefthanded individuals (Knecht et al, 2000;Rasmussen & Milner, 1977). The association between hand preference and language dominance has led to a number of evolutionary and biological theories proposing that hemispheric specialization and language (or perhaps other higher cognitive functions) coevolved and are unique characteristics of the human brain (see Annett, 1985;Corballis, 1992Corballis, ,2002Crow, 1998;Yeo, Thoma, & Gangestad, 2002, for reviews).…”
mentioning
confidence: 99%